A Time-Mode Neural Network Architecture - Crowley, Liam. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Electrical Engineering.; Advisor: Sameer Sonkusale.; Committee: Jeffery Hopwood, and Gouqing Fu.; Keyword: Electrical engineering.; In this work I present an energy efficient mixed-signal realization of a quantized neural network. In this implementation I represent signals in the time domain. By encoding signals as pulse-widths, we can take advantage of the extremely accurate clocks and delay resolution in nanometer CMOS processes. Weights are represented as binary weighted current sources with local DRAM storage. Capacitive integration implements weighted addition, and an inverter provides as rectified linear activation. I present the design in 0.18um CMOS process with successful circuit and behavioral simulation results on the IRIS dataset.